Strengthening seed value chains: Persistent challenges and ways forward - Donovan, Jason; Rutsaert, Pieter; Mausch, Kai; Almekinders, Conny; Akpo, Essegbemon; McEwan, Margaret; Shikuku, Kelvin Mashisia; Coaldrake, Peter; Delaquis, Erik; Gatto, Marcel; Hellin, Jonathan; Lillesø, Jens-Peter Barnekow; et al. (2021)
Slide deck prepared as input for the One-CGIAR Strategy on Seed Systems Development.